2019
DOI: 10.7150/ijbs.30611
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-322 Regulates Self-renewal of Mouse Spermatogonial Stem Cells through Rassf8

Abstract: Spermatogonial stem cells (SSCs) are essential for spermatogenesis and male fertility. MicroRNAs (miRs) are key regulators of gene expression involved in self-renewal, differentiation, and apoptosis. However, the function and mechanisms of individual miR in regulating self-renewal and differentiation of SSCs remain unclear. Here, we report for the first time that miR-322 regulates self-renewal of SSCs. Functional assays revealed that miR-322 was essential for SSC self-renewal. Mechanistically, miR-322 promoted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 48 publications
2
25
0
Order By: Relevance
“…Furthermore, the ability of cultured cells for self-renewal and colony formation also confirmed that the cells were undifferentiated. These results were consistent with other studies [ 4 , 6 , 14 ]. According to the literature, Sertoli cells as the only somatic cells in the seminiferous tubules play vital roles in the regulation of the balance between SSCs self-renewal and differentiation by secreting many growth factors [ 40 ].…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Furthermore, the ability of cultured cells for self-renewal and colony formation also confirmed that the cells were undifferentiated. These results were consistent with other studies [ 4 , 6 , 14 ]. According to the literature, Sertoli cells as the only somatic cells in the seminiferous tubules play vital roles in the regulation of the balance between SSCs self-renewal and differentiation by secreting many growth factors [ 40 ].…”
Section: Discussionsupporting
confidence: 94%
“…In line with this study, Chen et al found that miR-202-3p inhibitor induced differentiation in SSCs through reducing the expression of Plzf and increasing the expression of Stra8, Dazl and Sycp3 [ 15 ]. Wang et al also found that transfection of miR-322 inhibitor led a significant decrease in Gfrα1, Etv5 and Plzf expression and a marked increase in the expression of C-kit, stra8 and Bcl6 in mouse SSCs [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several miRNAs have been identified in spermatozoa that have implications as critical regulators of apoptosis (Capra et al, ; Dai et al, ; Lv et al, ; Ma et al, ). Apoptosis regulates spermatogenesis (Wang, Li, Gong, Zhao, & Wu, ) and spontaneous programmed cell death in mature spermatozoa (Aitken & Baker, ; Engel, Springsguth, & Grunewald, ). Through analysis of miRNAs in sperm samples, researchers demonstrated their expression patterns in spermatozoa in different mammals including human (Heidary, Zaki‐Dizaji, Saliminejad, & Khorram Khorshid, ; Krawetz et al, ), boar (Godia et al, ), mouse (Hutcheon et al, ) and bull (Fagerlind et al, ).…”
Section: Discussionmentioning
confidence: 99%